Clinical and epidemiological studies on 252 cases of acute hepatitis A during the past 15 years - WASADA, Mitsuru; SIRAISHI, Koichi; NAKANO, Atsushi; NISHIZAKI, Yasuhiro; UCHIYAMA, Junzo; ITAKURA, Masaru; MATSUZAKI, Shohei; WATANABE, Norihito; KOBAYASHI, Fuminori; NAGATA, Naruhiko; OKAZAKI, Yuhaku; KAGAWA, Tatehiro (Kanzo, 1996)
Retrospective studies on 252 cases of acute hepatitis A admitted from 1980 to 1994 was done to elucidate its clinical features in recent years. The occurrence of acute hepatitis A was periodic, and most frequent in 1990 during the past 15 years. The patients, especially females has been increased in number for the recent 5 years. They tended to be older than before. There were 6 prolonged cases of acute hepatitis A in which liver dysfunction continued over 3 months up to 7 months. None of them progressed to chronic hepatitis. It is of special interest that 6 cases of severe type of acute hepatitis A whose prothrombin time is less than 40% has been recognized in the recent two years. The severe type occurred frequently in male and aged patients. It is therefore suggested that the number of patients with acute hepatitis A is increased in older persons and females, and that severe type of acute hepatitis A has occurred recently.